The Domestic Balassa–Samuelson Effect of Inflation For the Greek Economy - Apergis, Nicholas (Taylor & Francis, 2013)
The goal of this study is to assess whether and to what extent inflation differentials between the tradable and nontradable sectors in the Greek economy are due to the domestic version of the Balassa–Samuelson (BS) effect and, therefore, the ‘expensiveness’ of the country and its huge deficit of international competitiveness. Using data over the period 1989 to 2009 from the Greek economy, the empirical results indicate that the domestic BS effect is present for the case of Greece and seems to explain about 33% of the overall inflation rate.